Formulation and Evaluation of Transdermal Patches Containing BGP-15 - Ildikó Bácskay; Zsolt Hosszú; István Budai; Zoltán Ujhelyi; Pálma Fehér; Dóra Kósa; Ádám Haimhoffer; Ágota Pető (MDPI AG, 2023)
BGP-15 is an active ingredient with many advantages, e.g., beneficial cardiovascular and anti-inflammatory effects. The transdermal administration of BGP-15 has great potential, which has not been investigated yet, despite the fact that it is a non-invasive and safe form of treatment. The aim of our study was to formulate transdermal patches containing BGP-15 and optimize the production with the Box-Behnken design of experiment. The most optimal formulation was further combined with penetration enhancers to improve bioavailability of the active ingredient, and the in vitro drug release and in vitro permeation of BGP-15 from the patches were investigated. FTIR spectra of BGP-15, the formulations and the components were also studied. The most optimal formulation based on the tested parameters was dried for 24 h, with 67% polyvinyl alcohol (PVA) content and low ethanol content. The selected penetration enhancer excipients were not cytotoxic on HaCaT cells. The FTIR measurements and SEM photography proved the compatibility of the active substance and the vehicle; BGP-15 was present in the polymer matrix in dissolved form. The bioavailability of BGP-15 was most significantly enhanced by the combination of Transcutol and Labrasol. The in vitro permeation study confirmed that the formulated patches successfully enabled the transdermal administration of BGP-15.